P.229 Epidemiology and Outcomes of Neck Pain Following Surgery for Degenerative Cervical Radiculopathy. (November 2021) - MacLean, MA; Dakson, A; Xavier, F; Christie, SD; Investigators, C
Abstract : Background: Many studies have demonstrated improved arm pain (AP) following surgery for degenerative cervical radiculopathy (DCR); however, axial neck pain (NP) is generally not felt to improve. The purpose of this study was to determine whether surgery for DCR improves NP. Methods: A ambispective cohort study of the Canadian Spine Outcomes Research Network (CSORN) registry for patients who received 1-level, 2-level, 3-level ADCF (anterior cervical discectomy and fusion) or cervical disc arthroplasty (CDA) for DCR. Outcomes: 12-month post-operative Visual Analogue Scale for NP (VAS-NP), Neck Disability Index (NDI), VAS for AP (VAS-AP), Short-Form Physical Health Composite Scale (SF36-PCS), and Mental Health Composite Scale (SF36-MCS). Results: We identified 603 patients with DCR. CDA patients were the youngest (ANOVA; p<0.001). Patients reported similar pre-operative AP, NP, disability, and health-related quality of life, regardless of procedure (ANOVA; all P>0.05). All procedures offered a statistically significant reduction in VAS-NP, VAS-AP, and NDI (ANOVA; all P<0.001). Mean change from baseline in NP, AP, and disability, were similar across procedures. At 12 months, mean reduction in VAS-AP, VAS-NP, and NDI exceeded minimal clinically important differences for nearly all procedures. Conclusions: Patients undergoing surgery for DCR can expect a clinically significant, approximate 50% reduction in NP, AP, and neck-related disability.